The impacts of network relationships on SMEs' internationalization process. - Mohamed, Mohd Zain; Ng, Siew Imm (Wiley-Blackwell, 2006)
In today's globalization era, more and more firms are striving to have an international presence, even though they face many challenges. Based on a multisite case study method, this article examines how indigenous Malaysian small and medium-sized enterprises (SMEs) use their network relationships to facilitate their internationalization process. The evidence from the case of three software firms and one control firm in this study support the firms' internationalisation process in the ways that network relationships trigger and motivate them to internationalize, influence their market-selection decision and mode-of-entry decision, help them gain initial credibility, allow access to additional relationships and established channels, help in lowering cost and reducing risk, and influence their internationalization pace and pattern.